A comparative study of electrocoagulation treatment with iron, aluminum and zinc electrodes for selenium removal from flour production wastewater. (September 2022) - Gong, Chenhao; Zhang, Jian; Ren, Xiaojing; He, Can; Han, Junxing; Zhang, Zhongguo
Abstract: Electrocoagulation (EC) using iron (Fe), zinc (Zn) and aluminum (Al) electrodes was comparatively applied in the treatment of selenium (Se) in flour production (FP) wastewater. It was indicated that EC treatment with Fe anode obtained highest removal efficiency (79.1%) for Se in the 90 min treatment in the comparative study, which could be attributed to the superior adsorption capacity of in-situ generated iron flocs. Removal of Se resulted from electrodeposition and adsorption to in-situ generated flocs in EC treatment, and the operational conditions significantly influenced the Se removal performance in this work. The results showed the acidic condition and higher current density favored EC treatment on Se removal, EC removed up to 97.8% of Se at pH 4 under 15 mA cm −2, whereas it obtained 83.5% and 50.4% of removal efficiency at pH 7 and 10, respectively. There was competitive adsorption in the process of selenium removal, as the in-situ generated flocs effectively removed 35.6% of humic acid-like (HA-like) substance in FP wastewater after 90 min treatment. The FTIR results showed that HA-like substance mainly contained the protein water hydrogen bond, carboxylate COO antisymmetric stretching and other functional groups. Through the analysis of existence of Se in flocs and wastewater, it can be found that approximately 2.8%–3.92% of Se was removed by electrodeposition process. This study illustrated the Se removal mechanism and provided constructive suggestion for food manufacturing to the metal removal and utilization of advanced treatment. Graphical abstract: Image 1 Highlights: The acidic condition and higher current density favored EC treatment on Se removal. EC (Fe) removed up to 79.1% of Se in the wastewater during 90 min treatment. The generated flocs had superior adsorption capacity on Se removal. Removal of Se resulted from electrodeposition and adsorption to generated flocs. Flour production wastewater was mainly composed of humic acid-like substance.